The The Effect Of Listening To Quran Recitation On Social-Emotional Development In Pre-School Children During Covid-19 Pandemic - firdaus firdaus; Rahmadaniar Aditya Putri; Andini Hardiningrum (Universitas Nahdlatul Ulama Surabaya, 2021)
Pandemics, which are elements of non-natural disasters, often have a prolonged impact on children, such as traumatic power. The biggest challenge for children with a pandemic is the growing risk that affects the development of cognitive, behavioral and emotional abilities. The purpose of this study was to analyze the effect of murottal Al-Qur'an therapy on social development in preschool children during the pandemic at TPQ Baitul Karim. The research design used Quasy-Experiment with pretest-posttest approach with control group design. The study population was all mothers and preschool children at TPQ Baitul Karim of 54 respondents. A sample size of 48 respondents was taken using the Cluster Sampling technique. The independent variable is Murottal Al-Quran therapy and the dependent variable is social emotional development. The instrument uses a questionnaire sheet. Data were analyzed by Mc.Nemar test and Chi-Square test with a significance ɑ = 0.05. The results showed that before being given murottal Al-Qur'an therapy, most of the treatment groups (66.6%) and control (58.3%) had unattainable social emotional development. The results after being given murottal Al-Qur'an therapy, most of the treatment groups (91.6%) and control (70.8%) had achieved social-emotional development. The results of the Mc.Nemar test analysis found ρ = 0,000, meaning ρ <ɑ then H0 was rejected, which means that there was an effect of Murottal Al-Qur'an therapy on social development. Chi Square test analysis showed that the value of ρ = 0.088, ρ> ɑ, then H0 is accepted, which means there is no difference in social emotional development between the treatment and control groups. Murottal Al-Quran therapy is effective for improving social emotional development. It is hoped that therapy can be applied to preschool children whose social emotional development is not achieved.